Motorization Affects and Density Lowers Indonesian Environmental Quality: Motorisasi Berdampak dan Kepadatan Penduduk Menurunkan Kualitas Lingkungan di Indonesia - Andreas Butarbutar; Ririt Iriani Sri Setiawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Environmental quality is increasingly pressured by daily human activities, demographic concentration, mobility growth, land conversion, waste generation, and fossil-fuel-based transportation. Specific Background: Indonesia experienced ecological challenges during 2018–2022, while motor vehicle growth and population density increased across provinces. Knowledge Gap: Previous studies on environmental quality commonly emphasized macroeconomic variables such as economic growth and industrialization, while direct human activity pressure through transportation mobility and demographic density remains less isolated in panel analysis. Aims: This study aimed to examine the relationship between motor vehicle numbers, population density, and the Environmental Quality Index across Indonesian provinces. Results: Using quantitative panel data from 34 provinces during 2018–2022 and the Fixed Effect Model selected through Chow and Hausman tests, the findings show that motor vehicle numbers had a positive and significant relationship with the Environmental Quality Index, with β = 0.0000065 and p = 0.0000. Population density had a negative and significant relationship, with β = −0.0223 and p = 0.0430. The model explained 87.689% of environmental quality variation. Novelty: This study isolates transportation mobility and demographic pressure as core human activity variables in Indonesian environmental quality analysis. Implications: The findings call for balanced policies that manage mobility growth, demographic pressure, and environmental protection while considering regional fiscal and ecological heterogeneity. Highlights: Vehicle numbers showed a positive significant coefficient. Demographic concentration reduced ecological carrying capacity. Provincial heterogeneity required Fixed Effect Model estimation. Keywords: JKB, Population Density, Environmental Quality